Silicon carbon negative electrode material, negative electrode plate, secondary battery, battery module, battery pack and power consumption device

JP7623390B6Active Publication Date: 2025-03-14CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022553153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-26
Publication Date
2025-03-14
Estimated Expiration
2041-09-26

Smart Images

  • Figure 0007623390000006
    Figure 0007623390000006
  • Figure 0007623390000007
    Figure 0007623390000007
  • Figure 0007623390000008
    Figure 0007623390000008
Patent Text Reader

Abstract

The present application provides a silicon-carbon negative electrode material, and a negative electrode plate, secondary battery, battery module, battery pack, and power consumption device each including the same. A battery is charged and discharged, and the battery includes a negative electrode made with the silicon-carbon negative electrode material described herein as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material. When a graph is plotted showing the relationship between the working electrode potential V and the differential value dQ / dV obtained by differentiating the charge / discharge capacity Q with respect to the working electrode potential V, when a current is applied to the negative electrode material in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, preferably 4 to 9, and more preferably 4.5 to 6.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of lithium batteries, and in particular to a silicon carbon negative electrode material and a method for producing the same, and a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device each having the same. [Background technology]

[0002] In recent years, as the application scope of lithium ion batteries expands, lithium ion batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment and aerospace. In the negative electrode material of lithium ion batteries, silicon carbon negative electrode materials have attracted attention due to their advantages such as very high theoretical specific capacity of silicon, low lithium storage reaction platform, and wide distribution in nature. However, as people's requirements for battery performance are becoming increasingly higher, how to further improve the gram capacity, first coulombic efficiency and cycle performance of silicon carbon negative electrode material batteries remains an urgent problem to be solved. Summary of the Invention

[0003] The present application has been made in view of the above-mentioned problems, and aims to provide a silicon carbon negative electrode material that will increase the initial coulombic efficiency of a battery using the silicon carbon negative electrode material, and improve the cycle performance and rapid charging performance.

[0004] To achieve the above object, the present application provides a silicon carbon negative electrode material and a manufacturing method thereof, as well as a negative electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device each including the same.

[0005] A first aspect of the present application provides a silicon carbon negative electrode material, and when a battery is charged and discharged, the battery being composed of a negative electrode made of the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material, and a graph of the relationship between the working electrode potential V and a differential value dQ / dV obtained by differentiating the charge / discharge capacity Q is plotted, when the negative electrode material is energized in the delithiation direction, a ratio of a maximum value Y of dQ / dV between 400 and 480 mV to a maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, optionally 4 to 9, and more optionally 4.5 to 6.5.

[0006] Batteries using the silicon carbon anode material of the present invention simultaneously have high gram capacity, high initial coulombic efficiency, and good cycle performance.

[0007] In any embodiment, optionally, in the X-ray diffraction chart (XRD pattern) of the silicon carbon negative electrode material of the present application, the ratio of the intensity of the peak at 2θ of 28.4 to the intensity of the peak at 2θ of 54.6 is 1.1 to 4.5.

[0008] In any embodiment, the silicon element content is optionally 2.5% to 10%, optionally 3% to 7%, based on the total weight of the silicon carbon negative electrode material. When the silicon element content is within the above range, the gram capacity of the battery using the silicon carbon negative electrode material of the present application is high and the cycle performance is good.

[0009] In any embodiment, the median particle size Dv50 of the silicon carbon negative electrode active material is optionally 10 μm to 15 μm, and optionally 11 μm to 14 μm. If the median particle size of the silicon carbon negative electrode material is too large, lithium may be precipitated during the cycle process, and cycle performance may be reduced, but if the median particle size of the silicon carbon negative electrode material is too small, the compression density may increase, the active material may not be sufficiently permeated by the electrolyte, and cycle performance may be reduced.

[0010] In any embodiment, optionally, the silicon carbon negative electrode material has no pores or the number of pores with a diameter of more than 50 nm in a single silicon carbon negative electrode material particle is less than 10. When the number of pores in the silicon carbon negative electrode material is within the above range, it helps to reduce side reactions at the void interface, thereby improving the first coulombic efficiency and improving the cycle performance.

[0011] In any embodiment, optionally, the specific surface area of ​​the silicon carbon anode material is greater than 1 m 2 ~3m 2 and selectively 1.1m 2 ~2m 2 When the specific surface area of ​​the silicon carbon negative electrode material is within the above range, there is a suitable number of reaction sites, which is conducive to reducing side reactions and improving kinetic performance.

[0012] A second aspect of the present application provides a method for producing a silicon carbon anode material, comprising: providing a silicon source and a carbon source; adding the silicon source and the carbon source to the additive solution, mixing uniformly, and removing the solvent to obtain a muddy mixture; Heating the slurry mixture to obtain a silicon carbon negative electrode material intermediate; and heating the silicon carbon negative electrode material intermediate under an inert gas atmosphere to obtain the silicon carbon negative electrode material. When a battery composed of a negative electrode made of the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material is charged and discharged, and a relationship graph is created between the differential value dQ / dV obtained by differentiating the charge / discharge capacity Q with respect to the working electrode potential V, when a current is passed through the negative electrode material in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, optionally 4 to 9, and more optionally 4.5 to 6.5.

[0013] The present manufacturing method has a simple process, a wide source of raw materials, and low cost, which is conducive to achieving large-scale industrial application.

[0014] In any embodiment, optionally, the median particle size Dv50 of the silicon source is 1 μm to 3 μm, and the median particle size Dv50 of the carbon source is 8 μm to 14 μm. When the median particle sizes of the silicon source and the carbon source are within the above ranges, the produced silicon carbon negative electrode material has an appropriate particle size range, which helps to improve the cycle performance of a battery using the silicon carbon negative electrode material.

[0015] In any embodiment, optionally, the additive is one or more selected from glucose, phenolic resin, sucrose, asphalt, polyacrylonitrile, sodium carboxymethylcellulose, polyvinylidene fluoride, and polytetrafluoroethylene.

[0016] In any embodiment, the heating condition of the muddy mixture is optionally pretreated at 100-400° C., optionally 100-300° C. for 2-6 hours. When heat-treated under the above conditions, the prepared silicon carbon negative electrode material is more conducive to improving the cycle performance of the battery.

[0017] In an optional embodiment, the heat treatment condition of the silicon carbon negative electrode material intermediate in an inert gas atmosphere is optionally heating at 600-1000° C. for 2-6 hours. The silicon carbon negative electrode material produced by the above heat treatment condition is more conducive to improving the cycle performance of the battery.

[0018] In any embodiment, the carbon source is optionally selected from the group consisting of graphite, coke, activated carbon, diamond, C 60 The graphite may be one or more selected from the above, and may optionally have a graphitization degree of 82% to 97%.

[0019] In any embodiment, optionally, the silicon source is one or more selected from elemental silicon, silicon oxide, silicate, optionally elemental silicon.

[0020] A third aspect of the present application provides an anode plate comprising the silicon carbon anode material according to the first aspect of the present application or produced by the method according to the second aspect of the present application.

[0021] A fourth aspect of the present application provides a secondary battery comprising the silicon carbon negative electrode material according to the first aspect of the present application, or the silicon carbon negative electrode material produced by the method according to the second aspect of the present application, or the negative electrode plate according to the third aspect of the present application.

[0022] A fifth aspect of the present application provides a battery module including the secondary battery according to the fourth aspect of the present application.

[0023] A sixth aspect of the present application provides a battery pack including one or more of the secondary battery according to the fourth aspect of the present application or the battery module according to the fifth aspect of the present application.

[0024] A seventh aspect of the present application provides a power consumption device including one or more of the secondary battery according to the fourth aspect of the present application, the battery module according to the fifth aspect of the present application, or the battery pack according to the sixth aspect of the present application.

[0025] The battery module, battery pack or power consuming device of the present application includes the secondary battery according to the fourth aspect of the present application, and therefore has at least the same advantages as the secondary battery according to the fourth aspect of the present application. [Brief description of the drawings]

[0026] [Figure 1] 1 is a graph showing the relationship between a differential value dQ / dV obtained by differentiating a working electrode potential V with a charge / discharge capacity Q and the working electrode potential V. [Diagram 2]Scanning electron microscope (SEM) images of typical non-porous (left) and porous (right) silicon carbon anode materials. [Diagram 3] 1 is an XRD pattern of a silicon carbon negative electrode material of Example 1. [Figure 4] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 4. [Figure 6] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 7] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 8] FIG. 8 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG. 7. [Figure 9] 1 is a schematic diagram of a power consuming device that uses a secondary battery as a power source according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the negative electrode active material and its manufacturing method, the negative electrode plate, the secondary battery, the battery module, the battery pack, and the electric device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of known matters and redundant description of substantially the same structure may be omitted. This is to avoid the following description from being unnecessarily long and to allow those skilled in the art to easily understand. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0028] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may or may not include the end values, and may be arbitrarily combined, i.e., any lower limit and any upper limit may be combined to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, they are expected to be understood as ranges of 60-110 and 80-120. Also, if ranges of 1 and 2 are listed as minimum values, and ranges of 3, 4, and 5 are listed as maximum values, the ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all expected. In this application, unless otherwise stated, the numerical range "a-b" represents a simple representation of any combination of real numbers between a and b, where a and b are all real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed herein, and "0-5" is merely a shorthand representation of combinations of these numerical values. Also, when a particular parameter is described as being an integer ≧2 or greater, this is equivalent to disclosing that the parameter is an integer, e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0029] Unless otherwise stated, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise stated, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0031] Unless otherwise stated, all steps in the present application may be performed in sequence, may be performed randomly, and are preferably performed in sequence. For example, the method includes steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method may further include step (c) means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), or may include steps (c), (a) and (b).

[0032] Unless otherwise stated, the terms "comprise" and "comprising" in this application may be open or closed. For example, the terms "comprise" and "comprising" may mean that the term may further include or include other components not listed, or may include or include only the listed components.

[0033] As used herein, the terms "greater than or equal to," "less than," "more than," and "less than" are inclusive, for example, "one or more" means one or more, and "one or more of A and B" means "A," "B," or "A and B."

[0034] In this application, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0035] In this application, the terms "median particle size" and "median particle size (Dv50)" are used interchangeably and refer to the particle size corresponding to when the cumulative particle size distribution rate of particles is 50%, and its physical meaning is that particles with a particle size larger than this value account for 50% and particles with a particle size smaller than this value also account for 50%, and is also called the median particle size.

[0036] In order to solve the problems of low initial coulombic efficiency, low gram capacity, poor cycle performance, etc. of batteries manufactured using silicon carbon negative electrode materials in the prior art, the inventors of the present application charge and discharge a battery consisting of a negative electrode manufactured using silicon carbon negative electrode materials as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material, and create a relationship graph between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q with the working electrode potential V and the working electrode potential V. As a result of extensive research, the inventors unexpectedly found that in the above relationship graph of the material, when the ratio of the maximum value Y of dQ / dV between 400-480mV and the maximum value X of dQ / dV between 200-255mV is 3.5-15, optionally 4-9, more optionally 4.5-6.5, the gram capacity of the secondary battery manufactured using the corresponding silicon carbon negative electrode material is high, the initial coulombic efficiency is high, and the cycle performance is good.

[0037] [Silicon carbon anode material] A first aspect of the present application provides a silicon carbon negative electrode material, and when a battery is charged and discharged, the battery being composed of a negative electrode made of the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material, and a graph of the relationship between the working electrode potential V and a differential value dQ / dV obtained by differentiating the charge / discharge capacity Q is plotted, when the negative electrode material is energized in the delithiation direction, a ratio of a maximum value Y of dQ / dV between 400 and 480 mV to a maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, optionally 4 to 9, and more optionally 4.5 to 6.5.

[0038] Although the mechanism is not yet clear, the inventors have unexpectedly found that by screening a silicon carbon anode material having a ratio of Y to X within the above range, the gram capacity, initial coulombic efficiency and cycle performance of a battery containing the silicon carbon anode material can be improved.

[0039] In some embodiments, optionally, in the X-ray diffraction chart of the silicon carbon negative electrode material described in the present application, the ratio of the intensity of the peak at 2θ of 28.4 to the intensity of the peak at 2θ of 54.6 is 1.1 to 4.5.

[0040] The XRD test of the silicon carbon negative electrode material of the present application may be performed by referring to a method commonly used by those skilled in the art, for example, in accordance with JIS K0131-1996 X-ray diffraction analysis general rules. For example, a Bruker D8 Discover type X-ray diffractometer manufactured by Bruker AxS in Germany is used, with CuKα light as the radiation source, light wavelength λ=1.5406 Å, scanning 2θ angle range of 20°-80°, and scanning speed of 4° / min.

[0041] In some embodiments, optionally, the content of elemental silicon in the silicon carbon negative electrode material is 2.5%-10%, optionally 3%-7%, based on the total weight of the silicon carbon negative electrode material.

[0042] Silicon element is useful for improving the gram capacity of silicon carbon anode material, thereby improving the energy density of the battery, but silicon element should not be too much, too much silicon may reduce the expansion and contraction performance of silicon carbon anode material, and the expansion of silicon carbon anode material may cause the loss of electrical contact with the current collector, thereby worsening the cycle performance of the battery. In addition, too much silicon element content may increase the gap of the adhesion part between particles, which may increase the repulsion of the plate.

[0043] In some embodiments, optionally, the content of carbon element in the silicon carbon negative electrode material is 80% to 97.5%, optionally 90% to 96.5%, based on the total weight of the silicon carbon negative electrode material.

[0044] The carbon element helps to reduce the deterioration of the expansion and contraction performance of the negative electrode material caused by the silicon element, thereby improving the cycle performance of the battery, but if the content of the carbon element is too high, it may reduce the gram capacity of the negative electrode material, thereby reducing the gram capacity of the battery.

[0045] In some embodiments, optionally the silicon carbon anode material has a median particle size Dv50 of 10 μm to 15 μm, optionally 11 μm to 14 μm.

[0046] If the median particle size of the silicon carbon negative electrode material is too large, on the one hand, the impedance increase may adversely affect the battery's fold performance, and on the other hand, lithium may precipitate during the cycle process, resulting in a decrease in the cycle performance of the battery. At the same time, if the median particle size of the silicon carbon negative electrode material is too large, the negative electrode material may expand and contract slightly, i.e., lose electrical contact with the current collector, thereby reducing the coulombic efficiency and cycle performance. Similarly, if the median particle size of the silicon carbon negative electrode material is too small, on the one hand, the electrochemical reaction sites of the material may increase, forming more SEI films and consuming more active lithium, thereby reducing the initial coulombic efficiency, and on the other hand, if the particle size is too small, the adhesion between particles may increase, leading to insufficient penetration of the active material electrolyte, resulting in a decrease in cycle performance.

[0047] As described above, the median particle size Dv50 of the silicon carbon negative electrode material of the present application has a meaning known in the art, and can be measured by an apparatus and method known in the art. For example, it can be easily measured using a laser particle size analyzer, referring to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method, for example, the Mastersizer 2000E type laser particle size analyzer of Malvern Instruments Limited.

[0048] In any embodiment, optionally, the silicon carbon anode material has no pores or has fewer than 10 pores with a diameter of more than 50 nm per single silicon carbon anode material particle.

[0049] The more pores in the silicon carbon anode material, the more side reactions will occur at the void interface, and the more active lithium and electrolyte will be consumed, which may reduce both the first coulomb efficiency and the cycle performance. At the same time, the voids may adsorb the electrolyte, resulting in insufficient electrolyte penetration of the active material, further reducing the cycle performance.

[0050] In this application, the scanning electron microscope test of the silicon carbon negative electrode material can be performed by the method commonly used in the field, for example, by testing with a ZEISS sigma 300 scanning electron microscope, and then testing with reference to standard JY / T010-1996.

[0051] In any embodiment, optionally, the specific surface area of ​​the silicon carbon anode material is greater than 1 m 2 ~3m 2 and selectively 1.1m 2 ~2m 2 It is.

[0052] The larger the specific surface area of ​​the silicon carbon anode material, the more active sites there are, which may increase side reactions and affect the cycle performance of the battery.Similarly, the smaller the specific surface area of ​​the silicon carbon anode material, the lower the kinetic performance and the more lithium precipitation in the battery, which may reduce the cycle performance.

[0053] The specific surface area of ​​the silicon carbon negative electrode material of the present application has a meaning known in the art and can be measured by instruments and methods known in the art. For example, the specific surface area of ​​a solid material is measured based on the gas adsorption BET method of GB / T 19587-2017, tested using the nitrogen adsorption specific surface area analysis test method, and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed by a Tri Star II 3020 type specific surface area and porosity analyzer manufactured by Micromeritics, USA.

[0054] A second aspect of the present application provides a method for producing a silicon carbon anode material, comprising: providing a silicon source and a carbon source; adding the silicon source and the carbon source to the additive solution, mixing uniformly, and removing the solvent to obtain a muddy mixture; Heating the slurry mixture to obtain a silicon carbon negative electrode material intermediate; and heating the silicon carbon negative electrode material intermediate under an inert gas atmosphere to obtain the silicon carbon negative electrode material. When a battery composed of a negative electrode made of the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material is charged and discharged, and a relationship graph is created between the differential value dQ / dV obtained by differentiating the charge / discharge capacity Q with respect to the working electrode potential V, when a current is passed through the negative electrode material in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, optionally 4 to 9, and more optionally 4.5 to 6.5.

[0055] In any embodiment, optionally, the silicon source has a median particle size Dv50 of 1 μm to 3 μm, and the carbon source has a median particle size Dv50 of 8 μm to 14 μm.

[0056] When the median particle size of the silicon source and the carbon source is within the above range, the silicon carbon negative electrode material produced by the method described herein has a high gram capacity and good cycle performance.

[0057] In any embodiment, optionally, the additive is one or more selected from glucose, phenolic resin, sucrose, asphalt, polyacrylonitrile, sodium carboxymethylcellulose, polyvinylidene fluoride, and polytetrafluoroethylene.

[0058] In an optional embodiment, optionally in the manufacturing method described herein, the silicon source and the carbon source are uniformly mixed in the additive solution by stirring.

[0059] In an optional embodiment, the solvent in the mixture is optionally removed by drying at 60 to 100° C. in the production method described herein.

[0060] In an optional embodiment, optionally in the production method described herein, the heating condition of the muddy mixture is 100 to 400° C., optionally 100 to 300° C., for 2 to 6 hours.

[0061] In any embodiment, optionally, in the manufacturing method described herein, the heat treatment condition of the silicon carbon negative electrode material intermediate in an inert gas atmosphere is heating at 600 to 1000° C. for 2 to 6 hours.

[0062] In any embodiment, optionally, in the manufacturing method described herein, the carbon source is selected from the group consisting of graphite, coke, activated carbon, diamond, C 60 The graphite may be one or more selected from the above, and may optionally have a graphitization degree of 82% to 97%.

[0063] In any embodiment, optionally in the manufacturing method described herein, the silicon source is one or more selected from elemental silicon, silicon oxide, and silicate, optionally elemental silicon.

[0064] In any embodiment, optionally, the weight ratio of the added amount of the silicon source to the added amount of the carbon source is 2% to 15%.

[0065] In any embodiment, optionally, the amount of the additive is 3% to 25% based on the total weight of the silicon source, the carbon source and the additive.

[0066] [Negative electrode plate] A third aspect of the present application provides an anode plate comprising the silicon carbon anode material according to the first aspect of the present application or produced by the method according to the second aspect of the present application.

[0067] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0068] As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on any one or two of the two opposing surfaces of the negative electrode current collector.

[0069] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymeric base layer and a metal layer formed on at least one surface of the polymeric substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0070] In some embodiments, in addition to the silicon carbon negative electrode material described in the first aspect of the present application, the negative electrode active material may further include a negative electrode active material for batteries known in the art. As an example, the negative electrode active material may further include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be at least one selected from elemental silicon, silicon oxide compound, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material may be at least one selected from elemental tin, tin oxide compound, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may further be used. These negative electrode active materials may be used alone or in combination of two or more.

[0071] In some embodiments, the negative electrode membrane layer optionally further comprises an adhesive, which may be at least one selected from styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0072] In some embodiments, the negative electrode membrane layer optionally further comprises a conductive agent, which may be at least one selected from superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0073] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0074] In some embodiments, the negative electrode plate can be manufactured as follows: The above-mentioned components for manufacturing the negative electrode plate, such as silicon carbon negative electrode active material, conductive agent, adhesive and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, and the negative electrode slurry is applied onto a negative electrode current collector, followed by processes such as drying and cold pressing to obtain a negative electrode plate.

[0075] [Positive electrode plate] In the present application, a secondary battery may be manufactured using a negative electrode plate and a positive electrode plate containing the silicon carbon negative electrode material of the present application, and a button battery may be manufactured using a negative electrode plate and a counter electrode containing the silicon carbon negative electrode material of the present application.

[0076] In some embodiments, metallic lithium is optionally used as the counter electrode to fabricate the button cell battery.

[0077] In some embodiments, a secondary battery is optionally manufactured using a positive electrode plate and a negative electrode plate comprising the silicon carbon negative electrode material of the present application.

[0078] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material according to the first aspect of the present application.

[0079] As an example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on any one or two of the two opposing surfaces of the positive electrode current collector.

[0080] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymeric material base layer and a metal layer formed on at least one surface of the polymeric material base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0081] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and modified compounds thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (also called LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (also called LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (also called LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622 (also called LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (also called LFP)), a complex of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a complex of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a complex of lithium iron manganese phosphate and carbon.

[0082] In some embodiments, the positive electrode membrane layer optionally further includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0083] In some embodiments, the positive electrode membrane layer optionally further comprises a conductive agent. For example, the conductive agent may comprise at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0084] In some embodiments, the positive electrode plate can be manufactured as follows: The above-mentioned components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector, followed by processes such as drying and cold pressing to obtain a positive electrode plate.

[0085] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. In the present application, the type of electrolyte is not particularly limited and may be selected according to needs. For example, the electrolyte may be in a liquid state, a gel state, or an all-solid state.

[0086] In some embodiments, the electrolyte uses an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.

[0087] In some embodiments, the electrolyte salt may be at least one selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorooxalate phosphate, and lithium tetrafluorooxalatophosphate.

[0088] In some embodiments, the solvent may be at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0089] In some embodiments, the electrolyte solution optionally further includes an additive. For example, the additive may include a negative electrode film-forming additive, may include a positive electrode film-forming additive, or may further include an additive that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.

[0090] [Separator] In some embodiments, the secondary battery further includes a separator. In the present application, the type of the separator is not particularly limited, and any known separator with a porous structure having good chemical stability and mechanical stability can be used.

[0091] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and is not particularly limited.

[0092] In some embodiments, the positive and negative plates and the separator can be formed into an electrode assembly by a winding or stacking process.

[0093] [Secondary battery] A fourth aspect of the present application provides a secondary battery comprising the negative electrode active material according to the first aspect of the present application, or the negative electrode active material produced by the method according to the second aspect of the present application, or the negative electrode plate according to the third aspect of the present application.

[0094] Typically, a secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During the charging and discharging process of the battery, active ions are inserted and released between the positive electrode plate and the negative electrode plate. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short circuit between the positive electrode and the negative electrode, while allowing the passage of ions.

[0095] In some embodiments, the lithium ion secondary battery may include an exterior body that can be used to package the electrode assembly and the electrolyte.

[0096] In some embodiments, the exterior of the lithium ion secondary battery may be a hard case, such as a hard plastic case, an aluminum case, or a steel case. The exterior of the lithium ion secondary battery may be a soft bag, such as a pouch-type soft bag. The material of the soft bag may be plastic, and examples of the plastic include polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0097] The secondary battery, battery module, battery pack, and power consuming device of the present application will be described below with appropriate reference to the drawings.

[0098] In the present application, the shape of the secondary battery is not particularly limited, and it may be cylindrical, rectangular, or any other shape. For example, FIG. 4 shows a secondary battery 5 having a rectangular structure as an example.

[0099] In some embodiments, referring to FIG. 5, the exterior body may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a storage cavity. The housing 51 has an opening communicating with the storage cavity, and the cover plate 53 can cover the opening to seal the storage cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the storage cavity. An electrolyte is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be selected by those skilled in the art according to specific practical needs.

[0100] In some embodiments, the lithium ion secondary battery may be assembled into a battery module, and the number of lithium ion batteries included in the battery module may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery module.

[0101] Fig. 6 shows an example of a battery module 4. Referring to Fig. 6, in the battery module 4, the lithium ion batteries 5 may be arranged in sequence along the length of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the lithium ion batteries 5 may be fixed by fastening parts.

[0102] Optionally, the battery module 4 may further include a casing having a storage space, in which the plurality of lithium ion batteries 5 are stored.

[0103] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0104] 7 and 8 show an example of a battery pack 1. Referring to Fig. 7 and Fig. 8, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper box 2 and a lower box 3, and the upper box 2 is covered by the lower box 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0105] The present application further provides a power consuming device, the power consuming device including at least one of the secondary battery, the battery module, or the battery pack according to the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, a satellite, an energy storage system, etc.

[0106] The power consumption device may be a secondary battery, a battery module or a battery pack depending on the usage needs.

[0107] 9 is an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module may be used to meet the need for high power and high energy density of the secondary battery of the power consuming device.

[0108] Other example devices may be mobile phones, tablet computers, notebook computers, etc. Such devices are typically required to be lightweight and thin, and may therefore use secondary batteries as a power source.

[0109] Working Example The following examples of the present application are described. The examples described below are illustrative and are merely for interpreting the present application, and cannot be understood as limiting the present application. In the examples, unless specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions shall be followed. Unless the manufacturer is specified, the reagents or equipment used are all general products available on the market.

[0110] The sources of raw materials for the examples of this application are as follows: [Table 1]

[0111] Example 1 40 g of glucose was dissolved in 200 ml of deionized water, and then 4.2 g of simple silicon with a median particle size Dv50 of 1.5 μm and 155.8 g of graphite with a median particle size Dv50 of 10 μm and a graphitization degree of 91% (named graphite 1) were added. The mixture was stirred at room temperature to mix uniformly, and the water solvent was removed by continuing stirring at 80° C. to obtain a muddy mixture. The muddy mixture was transferred to a heat treatment furnace at a temperature of 150° C. and pretreated for 240 minutes to obtain a silicon carbon negative electrode material intermediate. The silicon carbon negative electrode material intermediate was heated at 900° C. for 240 minutes in a nitrogen atmosphere. After cooling to room temperature, the obtained solid was crushed to obtain the required silicon carbon negative electrode material.

[0112] [Opposite] A lithium metal sheet is used as the counter electrode.

[0113] [Electrode plate manufacturing] The silicon carbon anode material of Example 1, acetylene black as a conductive agent, CNT (carbon nanotube) as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethyl cellulose (CMC) as a thickener were dissolved in deionized water as a solvent in a weight ratio of 92:2:0.5:4.5:1, and stirred to mix uniformly to prepare an anode slurry. The anode slurry was 6 mg / cm.2 The mixture was uniformly applied onto a copper foil serving as a negative electrode current collector in an amount of 100g, and then dried, cold pressed, and slitted to obtain a negative electrode plate.

[0114] [Electrolyte production In a glove box with an argon atmosphere (HO<0.1ppm, O<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed uniformly in a volume ratio of 3 / 7, fluoroethylene carbonate (FEC) was added at 10% (based on the weight of the ethylene carbonate / ethyl methyl carbonate organic solvent), and LiPF6 lithium salt was further added at 12.5% ​​(based on the weight of the ethylene carbonate / ethyl methyl carbonate organic solvent) to dissolve in the organic solvent, and the mixture was stirred uniformly to obtain the electrolyte solution of Example 1.

[0115] [Separator] A polyethylene (PE) membrane is used as the separator.

[0116] [Manufacturing of button batteries] The counter electrode, separator, and negative electrode plate were stacked in this order, and a separator was placed between the counter electrode and the negative electrode plate to separate them, and then the stack was rolled up to obtain a bare cell. The bare cell was placed in an outer casing, and the mixed basic electrolyte was injected and packaged to obtain a button battery.

[0117] The manufacturing conditions of other examples and comparative examples of the present application are shown in Tables 1 and 3. The [counter electrode], [production of electrode plate], [production of electrolyte], [separator] and [production of button battery] in the above examples and comparative examples are all the same as the process of Example 1.

[0118] [Test related parameters] Testing for Gram Capacity, First Coulombic Efficiency and Cycle Capacity Retention At 25°C and normal pressure, the button battery was discharged at a constant current of 0.1C to 0.005V, then discharged at a constant current of 0.04C to 0.005V and left to stand for 10 minutes, the discharge capacity at this time was recorded as the lithium insertion capacity of the first cycle, and then charged at a constant current of 0.1C to 1.5V and left to stand for 10 minutes, which is one cycle of charge and discharge process, the charge capacity at this time was recorded as the lithium removal capacity of the first cycle and defined as the gram capacity of the material. The button battery was subjected to 50 cycle charge and discharge tests using the above method, and the lithium removal capacity for each cycle was recorded. Initial Coulombic Efficiency (%) of a button cell = 1st cycle lithium removal capacity / 1st cycle lithium insertion capacity × 100% Cycle capacity retention rate (%) of a button battery = de-lithiation capacity at the 50th cycle / de-lithiation capacity at the 1st cycle × 100%.

[0119] Silicon Element Content Test The silicon element content in the anode material of the present application can be measured using instruments and methods known in the art. For example, the silicon carbon anode material is decomposed with reference to EPA-3052-1996 "Microwave Acid Decomposition Method for Silicates", and then the silicon element content is measured using an ICAP-7000 type inductively coupled plasma optical emission spectrometer (ICP-OES) from Thermo Fisher Scientific, USA, according to EPA 6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectroscopy". As a specific test method, 0.5 g of a silicon carbon anode material sample is decomposed by microwave using 10 mL of nitric acid with a mass fraction of 65% and 10 mL of hydrofluoric acid with a mass fraction of 40%, and after decomposition, it is added to a measuring flask of 50 mL to be constant, and then the silicon element content is measured using an ICAP-7000 type ICP-OES.

[0120] Method for measuring internal voids in silicon particles 1. The silicon carbon negative electrode material was prepared into a slurry, which was then applied onto a current collector and dried to produce an electrode plate. 2. The negative electrode plate was cut using plasma cutting technology to obtain a neat cross section, which was then placed under a scanning electron microscope equipped with an energy dispersive spectroscopy (EDS) device for observation. Five complete silicon particles with a diameter of >800 nm (the diameter of the circumscribed circle of the particle outline was taken as the diameter of the particle) were randomly selected and analyzed. 3. For each silicon particle, the particle components are analyzed using energy dispersive analysis technology. Whether it is silicon particle or not is judged based on the particle components. The judgment standard of silicon particles in the following examples is that if the silicon element content of the particle is ≧7wt%, it is judged to be silicon particle. 4. The voids inside each silicon particle were measured. The measurement method was as follows: first, the voids at the edge of the SEM image were not recorded as a number, but only the number of voids inside the SEM image was recorded. The diameter of the circumscribed circle of the void inside the silicon particle was defined as the diameter of the void. If the diameter of the void is ≧50 nm, it was recorded as 1 until all the voids inside the particle were completely measured. The number of all the voids inside the particle was summed up, and the sum was defined as the total number of voids inside the silicon particle.

[0121] Graphitization degree test The graphitization degree of the graphite described herein can be tested by methods known in the art. For example, the graphitization degree may be tested by an X-ray diffractometer (Bruker D8 Discover), which refers to JIS K 0131-1996, JB / T 4220-2011 to measure the magnitude of d002, and then calculate the graphitization degree based on the formula G=(0.344-d002) / (0.344-0.3354), where d002 is the interlayer spacing in the artificial graphite crystal structure expressed in nano (nm).

[0122] [Table 2]

[0123] [Table 3]

[0124] As can be seen from Tables 1 and 2, the batteries manufactured with the silicon carbon negative electrode materials of Examples 1 to 11 have high gram capacity, high initial coulombic efficiency, and good cycle capacity retention.

[0125] As can be seen from Examples 1 to 11, when the Y / X ratio of the silicon carbon negative electrode material is within the range of 3.5 to 15, the cycle capacity retention rate of the secondary battery is clearly superior to that of Comparative Examples 1 to 3, in which the Y / X ratio is not within the range.

[0126] As can be seen from Examples 1 to 5 and Comparative Example 2, as the content of silicon element gradually increases, the gram capacity of the secondary battery also increases, but when the silicon content exceeds 10% (Comparative Example 2), the cycle capacity retention rate of the secondary battery obviously decreases.

[0127] As can be seen from Examples 3 and 6-9, as the graphitization degree of the carbon source is from 70% to 99%, the gram capacity of the corresponding battery gradually increases, and the initial coulombic efficiency and cycle capacity retention rate first improve and then decrease. When the graphitization degree of the carbon source is from 82% to 97%, the overall performance of the battery is good.

[0128] As can be seen from Examples 10 and 7, Examples 3 and 11, Examples 8 and 12, as the pretreatment temperature increases from 100° C. to 400° C., the gram capacity and initial coulombic efficiency of the corresponding batteries gradually decrease, but the cycle capacity retention improves first and then decreases. As can be seen from Example 3 and Comparative Example 1, as the pretreatment temperature increases from 150° C. to 500° C., the performances of the corresponding batteries are obviously deteriorated.

[0129] [Table 4]

[0130] [Table 5]

[0131] As can be seen from Tables 3 and 4, Examples 14 to 24 are clearly superior to Comparative Examples 4 to 6 in terms of gram capacity, initial coulombic efficiency, and cycle capacity retention.

[0132] As can be seen from Examples 14 to 16 and Comparative Example 4, when the number of pores with a diameter of more than 50 nm in a single silicon carbon negative electrode material is 10 or less, the performance of the battery does not change obviously, but as the number of pores increases to 30, the gram capacity and initial coulombic efficiency decrease obviously, and the capacity retention rate after 50 cycles decreases more obviously.

[0133] As can be seen from Examples 17-20 and Comparative Example 5, when the median particle diameter Dv50 of the silicon carbon negative electrode material is 10 μm-15 μm, the battery performance is superior to that when the median particle diameter is 18 μm. When the median particle diameter is 11 μm-14 μm, the improvement in battery performance is more obvious.

[0134] As can be seen from Examples 21 to 24 and Comparative Example 6, the specific surface area of ​​the silicon carbon negative electrode material is 1 m 2 ~3m 2 The performance of the battery with a specific surface area of ​​1.1 m is better than that of the battery with a specific surface area of ​​3.5. 2 ~2m 2 , the improvement to the battery performance becomes more evident.

[0135] As described, the present application is not limited to the above embodiments. The above embodiments are merely illustrative, and any embodiment that has substantially the same configuration as the technical concept and achieves the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, other forms that add various modifications that a person skilled in the art can conceive of to the embodiments or combine some components of the embodiments without departing from the scope of the gist of the present application are also included in the scope of the present application. [Explanation of symbols]

[0136] 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate

Claims

1. A silicon carbon negative electrode material containing silicon and carbon elements, When a battery composed of a negative electrode manufactured using the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material is charged and discharged, and a graph of the relationship between the differential value dQ / dV obtained by differentiating the charge / discharge capacity Q with respect to the working electrode potential V and the working electrode potential V is created, when a current is passed through the silicon carbon negative electrode material in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15, The silicon carbon negative electrode material has no pores or the number of pores with a diameter of more than 50 nm in a single silicon carbon negative electrode material particle is less than 10; The content of the silicon element is 2.5% to 10% based on the total weight of the silicon carbon negative electrode material; The median particle size Dv50 of the silicon carbon negative electrode material is 10 μm to 15 μm; The specific surface area of ​​the silicon carbon negative electrode material is 1 m 2 ~3m 2 Silicon carbon anode material.

2. 2. The silicon carbon negative electrode material according to claim 1, wherein the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV when the silicon carbon negative electrode material is energized in the delithiation direction is 4 to 9.

3. When the silicon carbon negative electrode material is energized in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 4.5 to 6.

5. The silicon carbon negative electrode material according to claim 1 or 2.

4. The silicon carbon negative electrode material according to any one of claims 1 to 3, wherein in an X-ray diffraction chart, the ratio of the intensity of the peak at 2θ of 28.4 to the intensity of the peak at 2θ of 54.6 is 1.1 to 4.

5.

5. The silicon carbon negative electrode material according to any one of claims 1 to 4, wherein the content of the silicon element is 3% to 7% based on the total weight of the silicon carbon negative electrode material.

6. The silicon carbon negative electrode material according to any one of claims 1 to 5, wherein the median particle diameter Dv50 of the silicon carbon negative electrode material is 11 μm to 14 μm.

7. The specific surface area of ​​the silicon carbon negative electrode material is 1.1 m 2 ~2m 2 The silicon carbon negative electrode material according to any one of claims 1 to 6.

8. A method for producing a silicon carbon anode material, comprising the steps of: providing a silicon source and a carbon source; adding the silicon source and the carbon source to the additive solution, mixing uniformly, and removing the solvent to obtain a muddy mixture; Heating the slurry mixture to obtain a silicon carbon negative electrode material intermediate; and heating the silicon carbon negative electrode material intermediate under an inert gas atmosphere to obtain the silicon carbon negative electrode material. When a battery is charged and discharged, the battery is composed of a negative electrode made of the silicon carbon negative electrode material as a working electrode, metallic lithium as a counter electrode, and an electrolyte containing a lithium ion conductive material. When the working electrode potential V is differentiated by the charge / discharge capacity Q to produce a graph of the relationship between the differential value dQ / dV and the working electrode potential V, the silicon carbon negative electrode material is energized in the delithiation direction. the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 3.5 to 15; The silicon carbon negative electrode material has no pores or the number of pores with a diameter of more than 50 nm in a single silicon carbon negative electrode material particle is less than 10; The method for producing a silicon carbon negative electrode material comprises heating the muddy mixture at 100 to 400° C. for 2 to 6 hours.

9. 9. The method of claim 8, wherein when the silicon carbon negative electrode material is energized in a delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is between 4 and 9.

10. The method according to claim 8 or 9, wherein when the silicon carbon negative electrode material is energized in the delithiation direction, the ratio of the maximum value Y of dQ / dV between 400 and 480 mV to the maximum value X of dQ / dV between 200 and 255 mV is 4.5 to 6.

5.

11. The method according to any one of claims 8 to 10, wherein the silicon source has a median particle size Dv50 of 1 µm to 3 µm, and the carbon source has a median particle size Dv50 of 8 µm to 14 µm.

12. The additive solution is one or more selected from a glucose solution, a phenolic resin solution, a sucrose solution, an asphalt solution, a polyacrylonitrile solution, a sodium carboxymethylcellulose solution, a polyvinylidene fluoride solution, and a polytetrafluoroethylene solution. The method according to any one of claims 8 to 11.

13. The method according to any one of claims 8 to 12, wherein the heating condition of the muddy mixture is pretreatment at 100 to 300°C for 2 to 6 hours.

14. The method according to any one of claims 8 to 13, wherein the heat treatment condition of the silicon carbon negative electrode material intermediate in an inert gas atmosphere is heating at 600 to 1000°C for 2 to 6 hours.

15. The carbon source is graphite, coke, activated carbon, diamond, C 60 The method according to any one of claims 8 to 14, wherein the compound is one or more selected from the group consisting of:

16. The method according to any one of claims 8 to 15, wherein the carbon source is graphite having a degree of graphitization of 82% to 97%.

17. The method according to any one of claims 8 to 16, wherein the silicon source is one or more selected from elemental silicon, silicon oxide, and silicate.

18. The method of any one of claims 8 to 17, wherein the silicon source is elemental silicon.

19. A secondary battery comprising the silicon carbon negative electrode material according to any one of claims 1 to 7.

20. 20. A power consuming device comprising the secondary battery of claim 19.

Citation Information

Patent Citations

  • Negative electrode material, negative electrode comprising same and preparation method thereof

    CN110828812A

  • Lithium ion secondary battery negative electrode material and lithium ion secondary battery

    JP2018147772A